Theoretical description of the decays Λb → ΛðÞð1 2 ; 3 2 Þ + J=ψ; Physical Review D; Vol. 96, iss. 1 - Gutsche T. Thomas; Ivanov M. A. Mikhail Alekseevich; Korner J. G. Juergen; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Lyubushkin V. V. Vladimir; Santorelli P. Pietro (2017, 2017)
Title screen